Smart Cartusing RFID and Weighing Load Cell Sensor for Shopping Malls - T.Gunasagar, Bhuvaneswari Balachander (International Journal of Advanced Science and Technology, 2020)
This paper implements a quick shopping cart using Radio frequency identification and weighing load cell sensors. Where rapid development of employment in wireless sensor networks(WSN) in the field of industrial related applications makes to create life less demanding tasks with respective of reliability, energy consumption and cost-effectiveness. The idea of quick shopping cart is suitable for use in many places like daily house hold needs, textiles etc.., Where this system helps in reducing the time and also human requirement for the owners. This helps in automatic bill generation of shopped products instead of standing for long hours in queue for bill payments. Where this makes the smart system attractive to both buyers and sellers[1]. The results of the system in retrieved by connecting the trolley to the end system and the information of the purchased products is delivered in form of digital message to the customers.